Crafting Low-Sugar Cosmos Ice Cream: Exploring Diverse Stabilizing Agent Combinations (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This research focuses on utilizing Cosmos caudatus (also known as ulam raja), a bioactive-rich plant, as the primary functional ingredient in ice cream formulations to develop a healthier dessert option. By following the standard ice cream protocol, two stabilizers (xanthan gum and Arabic gum) were used at different ratios, and CMC served as a positive control for the experiment. To determine the optimal conditions, the finished goods were subjected to physicochemical, overrun, and melting tests, and sensory analysis. The results show that the optimal formulation for a low-sugar Cosmos caudatus ice cream (LSCI) was achieved at a ratio of 0.75:0.25 between xanthan gum and Arabic gum. The use of optimal stabilizer formulation in developing LSCI had no significant effect on the pH value. However, the viscosity of the optimal formulation was higher than that of the control formulation. A ratio of 0.75:0.25 resulted in lower hardness, higher firmness, and cohesiveness in the texture profile analysis. In terms of colour, aroma, texture, taste, and overall acceptability, the use of an optimal stabilizer formulation on the LSCI outperformed the control stabilizer formulation in all areas. In conclusion, the study identifies the optimal stabilizer formulation (0.75 xanthan gum, 0.25 Arabic gum) for low-sugar Cosmos caudatus ice cream, showcasing improved texture and sensory attributes compared to the CMC control. This underscores the potential of this formulation to enhance both the quality and consumer appeal of healthier ice cream options.
Keywords: Cosmos caudatus; Stabilizer optimization; Sensory analysis; Low-sugar dessert; Gums